Tipula (Vestiplex) levisoni sp. nov., a new cranefly (Diptera, Tipulidae) from the Western Himalayas - Starkevich, Pavel; Podėnas, Sigitas; Sivell, Duncan (Zootaxa, 2022)
A new cranefly, Tipula (Vestiplex) levisoni sp. nov., is described and illustrated based on males and females collected in India and Nepal. The illustrations of male and female genitalia for the most closely related regional species, T. (V.) tanycera Alexander, 1961 and T. (V.) mitchelli Edwards, 1927 are also provided. The female of T. (V.) mitchelli is described for the first time.